2023
DOI: 10.3390/genes14030638
|View full text |Cite
|
Sign up to set email alerts
|

Short Insertion and Deletion Discoveries via Whole-Genome Sequencing of 101 Thoroughbred Racehorses

Abstract: Thoroughbreds are some of the most famous racehorses worldwide and are currently animals of high economic value. To understand genomic variability in Thoroughbreds, we identified genome-wide insertions and deletions (INDELs) and obtained their allele frequencies in this study. INDELs were obtained from whole-genome sequencing data of 101 Thoroughbred racehorses by mapping sequence reads to the horse reference genome. By integrating individual data, 1,453,349 and 113,047 INDELs were identified in the autosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“… *DB101: Allele frequency was extracted from a whole-genome variant database from 101 Thoroughbred horses (Tozaki et al ., 2023 [ 23 ]).PE: probability of exclusion, PD: power of discrimination, PID: probability of identity. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… *DB101: Allele frequency was extracted from a whole-genome variant database from 101 Thoroughbred horses (Tozaki et al ., 2023 [ 23 ]).PE: probability of exclusion, PD: power of discrimination, PID: probability of identity. …”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we identified 12,173,068 SNVs and 1,566,396 INDELs in a population of 101 Thoroughbreds [ 22 , 23 ]. Approximately 7.77 times fewer INDELs were detected than SNVs, indicating that they are less likely to occur than single-base substitutions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations